The blue in Portuguese historical azulejos - Fares, M. (2012)
Although Portuguese azulejos are such an important heritage asset, having been extensively studied from the Art Historian viewpoint, the knowledge concerning the raw materials used and the details of the technological manufacturing process is very limited. The research project behind this dissertation was aimed at improving the present knowledge as concerns the composition of the blue pigment used in the 17th and 18th centuries. A representative set of azulejos spanning at least 200 years from ca. 1600 to 1800 was selected and the composition of the blue colour in their glazes analysed. The results were assessed aiming to answer the following main questions: i- What are the characteristic compositions of the colour (pigment and impurities) and how do they relate with the chronology of the azulejos? ii- What are the compositional traits that bear on the shades of the blue colour? iii- Can Portuguese azulejos be separated from Dutch and Spanish productions, at times when they co-existed in Portugal, solely by the composition of the blue colour? iv- Is the composition of the blue colour related with provenance of azulejos within Portugal? v- Are there grounds to suspect that at some time the Portuguese used, besides the well-known German zaffre, alternative sources of blue colour imported through their wide sea trade routes?